Kritična analiza uporabe anglo-ameriških dokumentov glede nasilja ob koncu druge svetovne vojne v Julijski krajini - Bajc, Gorazd (Studia Historica Slovenica, 2017)
The article critically analyses the historians' use and interpretation of Anglo-American archival documents, important sources for researching the complex problem of Yugoslav administration after-war violence in Venezia Giulia, e.g. "foibas" and the fate of deported people. Basing on a systematic review of British and American primary sources, the authors present the problem of their accessibility and the use of an interpretative key for their understanding. They emphasize the methodological and theoretical questions or key preconditions for the discussion of this content, which have mostly not been considered in recent research. In the second part of the article individual examples of documents, which have already been used by the historians, are presented. However, when researches used those documents, they failed to consider other, similar documents.
Keywords: arhivsko gradivo; dokumenti; druga svetovna vojna; Italija; Jugoslavija; Julijska krajina; nasilje; svetovna vojna 1939-1945; Velika Britanija; ZDA